OP0202 Gene expression profiles in primary sjÖgren's syndrome with and without systemic manifestations. (12th June 2018) - Vitali, C.; Dolcino, M.; Andracco, R.; Pelosi, A.; Fiore, P.; Maglione, W.; Zaccara, E.; Del Papa, N.; Puccetti, A.
Abstract : Background: Different phenotypes characterise the clinical spectrum of primary Sjögren's syndrome (SjS). Patients with a clinical expression limited to glandular features (GFs) are classically distinguished from patients with extra-glandular manifestations (EGMs). The former patients often complain higher level of fatigue and widespread pain (WP). (Segal et al. 2013) This suggests that gene expression pattern may be different in the two subgroups. Objectives: To investigate the differences of gene expression in SjS patients with GFs and in those with EGMs. Methods: Nineteen patients with SjS were selected for the study. Gene expression in peripheral blood mononuclear cells (PBMCs) was analysed in 4 patients with EGMs and 4 patients with GFs alone using Clariom D human Affymetrix gene chip (Affymetrix, Santa Clara, CA, USA), and compared to that found in healthy controls. Differences in gene expression were evaluated by analysis of variance (ANOVA) and Step-Up FDR-controlling procedure, being FDR corrected p value≤0.01 and fold change >2 considered as statistically significant. Validation of the gene overexpression was performed by quantitative Real Time(qRT)-PCR in PBMCs from all the selected SjS patients, using the ΔΔCt method for comparing relative fold expression differences. Results: All the enrolled SjS patients (18 females and 1 male) had a positive lip biopsy, while anti-SSA/Ro antibodies were detected in 10/11 and 6/8 of the patients with EGMs and with GFs alone, respectively. ESSDAI value ranged from 7 to 55 in patients with EGMs (median 17), and from 0 to 2 in patients with GFs alone (median 1). In both types of patients, the functional analysis of the two transcriptomes showed a large number (>1000) of modulated genes that are involved in the well-known pathological processes of SjS, i.e., apoptosis, inflammatory response, immune response, type I and type II interferons, and Toll-like receptors signalling. Genes modulated only in patient with EGMs showed a significant enrichment of the biological processes associated with immune response (79% of all enriched processes) and, namely, of the molecular pathways related to B cell activation. The analysis of the transcripts expressed only in patients with GFs alone showed instead a preponderant enrichment in different metabolic processes (43%) and in processes associated with the central perception of the stimuli. Indeed, genes involved in sensory perception and in nociceptive signals (i.e., ANPEP, TNRF1, P2RY1, IFNG) were modulated exclusively in patients with GFs alone. The significant differential expression of selected genes in the two SjS subgroups was confirmed by the qRT-PCR analysis. Conclusions: These data indicate that in SjS patients with GFs alone a dysregulation of pain pathways (namely beta-adrenergic receptor and Notch signalling) may play a role in the development of WP that is common in this subset of patients. The biological mechanisms triggering the activation of these genes remain to be completely clarified. Disclosure of Interest: None declared